A new species of Xestia Hübner, 1818 (Lepidoptera, Noctuidae) from China - Gyulai, Péter (Zootaxa, 2018)
The genus Xestia Hübner, 1818 is supposedly a polyphyletic Noctuinae genus, seems to be a complex of lineages, of which the species are often remarkably different externally. Most of the described species are Holarctic. During the last twenty years, 21 new Xestia species and one new subspecies have been described from the eastern Palaearctic (Hreblay, Ronkay, & Plante (1998), Hreblay & Ronkay (1998), Gyulai & Ronkay (2001), Gyulai, Ronkay, & Saldaitis (2011, 2013), Gyulai & Ronkay (2016), Gyulai (2017)).